Мобильные прямопоисковые технологии: факты обнаружения и локализации каналов вертикальной миграции флюидов - дополнительные свидетельства в пользу глубинного синтеза углеродов - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н.; Прилуков, В.В. (Геоінформатика, 2016)
Анализируются результаты апробации прямопоискового метода частотно-резонансной обработки и декодирования данных дистанционного зондирования Земли (ДЗЗ) на Шебелинском газоконденсатном месторождении (ГКМ), Украина, а также поисков каналов вертикальной миграции глубинных флюидов на месторождениях углеводородов (УВ) и в пределах аномальных зон типа “залежь УВ” в различных регионах мира. Предложена методика оперативного обнаружения вертикальных каналов миграции флюидов. В районе Шебелинского ГКМ закартирована аномальная зона площадью 224,5 км² типа “газ + конденсат”, а также выявлены два вертикальных канала миграции флюидов с давлением 280 и 272 МПа. В зоне одного из каналов зарегистрированы отклики на резонансных частотах нефти, газа, конденсата, гелия, водорода, углекислого газа. В пределах более крупного участка (2220 км²) закартировано семь аномальных зон общей площадью 259,9 км². Вертикальные каналы обнаружены также на площади структуры “вихревого” типа в Западной Сибири, в пределах Мачухского газового месторождения в Днепровско-Донецкой впадине, в районе аварийной скважины в Мексиканском заливе, в контурах аномалий типа “нефть + газ” в районе газового месторождения Зохр в Средиземном море. Приведенные факты обнаружения каналов вертикальной миграции флюидов, а также наличие значительного количества аномальных зон типа “залежь нефти и газа” в различных горизонтах (в том числе в глубинных) разреза можно считать важными аргументами в пользу абиогенного происхождения УВ. Проаналізовано результати апробації прямопошукового методу частотно-резонансної обробки та декодування даних дистанційного зондування Землі (ДЗЗ) на Шебелинському газоконденсатному родовищі (ГКР), Україна, а також пошуків каналів вертикальної міграції глибинних флюїдів на родовищах вуглеводнів (ВВ) і в межах аномальних зон типу “поклад ВВ” у різних регіонах світу. Запропоновано методику оперативного виявлення вертикальних каналів міграції флюїдів. У районі Шебелинського ГКР закартовано аномальну зону площею 224,5 км2 типу “газ + конденсат”, а також виявлено два вертикальні канали міграції флюїдів з тиском 280 і 272 МПа. У зоні одного з каналів зареєстровано відгуки на резонансних частотах нафти, газу, конденсату, гелію, водню, вуглекислого газу. В межах більшої ділянки (2220 км²) виявлено сім аномальних зон загальною площею 259,9 км². Вертикальні канали виявлено також на площі структури “вихрового” типу в Західному Сибіру, в межах Мачуського газового родовища у Дніпровсько-Донецькій западині, в районі аварійної свердловини в Мексиканській затоці й у контурах аномалій типу “нафта + газ” у районі газового родовища Зохр у Середземному морі. Наведені факти виявлення каналів вертикальної міграції флюїдів, а також наявності значної кількості аномальних зон типу “поклад нафти і газу” в різних горизонтах (у тому числі глибинних) розрізу можна вважати важливими аргументами на користь абіогенного походження ВВ. Purpose. The article has several objectives: to test advanced direct-prospecting method of frequency-resonance processing and decoding of RS data on the large Shebelinka GCF (Ukraine); to search for and localize vertical channels of deep fluids migration within the hydrocarbon fields and mapped anomalous zones of the “deposit of hydrocarbons” type in various regions of the world: the Dnieper-Donets Basin, Western Siberia, the Gulf of Mexico, and the Mediterranean Sea; to develop a method to detect vertical channels of fluid migration; to improve the methodological principles of applying direct-prospecting geophysical methods and technologies during hydrocarbon accumulations prospecting in reservoirs of traditional and non-traditional types.
Design/methodology/approach. In conducting the experimental research we used mobile technology of frequency- resonance processing of satellite images. It is based on the principles of the “matter” paradigm of geophysical studies and permits to detect and map operatively the anomalous zones of the “deposit of hydrocarbons (oil, gas and gas condensate)” type. A particular method of this technology allows us, within the contours of the detected anomalous zones at resonance frequencies of gas, to estimate the maximum value of the fluid pressure in the reservoirs at different intervals (including depth) of the cross-section.
Findings. In the region of the Shebelinka GCF location, we have mapped an anomalous zone of 224,5 km² area of the “gas + condensate” type with reservoir pressures in the range of 20,4—25,8 MPa. In the north-western and south-eastern parts of the field, we have found two vertical channels of fluid migration with the reservoir pressure of 280 and 272 MPa. Within the vertical channels, we have registered areas of anomalous responses at resonant frequencies of oil, gas, condensate, helium, hydrogen and carbon dioxide. Additionally, within a larger area (2220 km²), we have detected and mapped seven separate anomalous zones with total area of 259,9 km². Relative to the observed area, all anomalous zones make up 21,82 %. A vertical channel with the pressure of 42,5 MPa was also found within the structure of “vortex” type in Western Siberia, and two additional channels (95,0 MPa and 110 MPa) within Machuhskoye gas field in the DDB. The vertical channel with a largest area was detected in the region of emergency well location in the Gulf of Mexico. The maximum value of the formation pressure within its contour was estimated at 165 MPa. Within two anomalous zones of the “Oil&Gas” type, found in the vicinity of the Zohr large gas field in the Mediterranean Sea, we have also mapped a vertical channel of depth fluids migration with the reservoir pressure of 141 MPa. The local sites in the areas of vertical channels location, identified within the contours of the anomalous zones, should be considered as the most promising for a detailed study by geophysical methods and location of prospecting wells.
Practical significance and conclusions. The results of these studies indicate the presence within the hydrocarbons fields and mapped anomalous zones of the “deposit of hydrocarbons” type of local areas with anomalously high formation pressure of fluids in the reservoirs of cross-section — the vertical channels of the deep fluids migration. Mobile and direct- prospecting methods allow us to identify and map operatively these channels using the results of anomalous responses registration on the resonant frequencies of helium, hydrogen, carbon dioxide. The tested methods of the vertical channels of fluid (HC) migration detecting and of reservoir pressures on different depths of cross-section evaluation can be widely used for the operative assessment of hydrocarbon potential of deep horizons of the cross-section. These facts of the vertical channels of fluid migration detection, as well as the presence of a significant number of anomalous zones of the “Oil and Gas deposit” type at different levels (including depth) of the cross-section can be regarded as important evidence in favor of the abiotic origin of hydrocarbons.